Detailed kinetic analysis and modelling of the dry gasification reaction of olive kernel and lignite coal chars. (15th April 2023) - Lampropoulos, Athanasios; Varvoutis, Georgios; Montes-Morán, Miguel A.; Menéndez, J. Angel; Konsolakis, Michalis; Marnellos, George E.
Abstract: The dry gasification process of solid fuels is a promising pathway to mitigate and utilize captured CO2 emissions toward syngas generation with tailored composition for several downstream energy conversion and chemical production processes. In the present work, comprehensive kinetic analysis and reaction modelling studies were carried out for olive kernel and lignite coal chars gasification reaction using pure CO2 as gasifying agent. Chars reactivity and kinetics of the gasification reactions were thoroughly examined by thermogravimetric analysis at three different heating rates and correlated with their physicochemical properties. The reactivity of olive kernel char, as determined by the mean gasification reactivity and the comprehensive gasification characteristic index, S, was almost three times higher compared to that of the lignite coal char. It was disclosed that the fixed carbon content and alkali index (AI) have a major impact on the reactivity of chars. The activation energy, Ea, estimated by three different model-free kinetic methods was ranged between 140 and 170 kJ/mol and 250–350 kJ/mol for the olive kernel and lignite coal chars, respectively. The activation energy values for the lignite coal char significantly varied with carbon conversion degree, whereas this was not the case for olive kernel char, where the activation energy remained essentially unmodified throughout the whole carbon conversion range. Finally, the combined Malek and Coats-Rendfrem method was applied to unravel the mechanism of chars-CO2 gasification reaction. It was found that the olive kernel char-CO2 gasification can be described with a 2D-diffusion mechanism function (D2) whereas the lignite coal char-CO2 gasification follows a second order chemical reaction mechanism function (F2). Highlights: Kinetic analysis and modelling of CO2 -gasification of OK800 and LG800 chars. OK800 showed better reactivity due to its higher fixed carbon and alkali index. LG800 exhibited substantially higher Ea for CO2 -gasification than OK800. CO2 -gasification of OK800 follows a single reaction 2D-diffusion mechanism. CO2 -gasification of LG800 is described by a 2 nd order reaction mechanism.